Biophysiological and biochemical parameters among patients with hypertension- A cross-sectional study - Betcy George; Porkodi Arjunan; Abraham M. Ittyachen; M. Rajkumar; N.A. Sheela Shenai; Soney Meleth Varghese; Ramesh Chandrababu (Clinical Epidemiology and Global Health)
Background: Research evidence highlights modifiable risk factors as key elements in preventing hypertension and its complications. This study explores their association with hypertension to inform preventive strategies. Objectives: We assessed the socio-clinical, bio-physiological, and biochemical parameters and its associated factors. Materials and methods: This hospital-based cross-sectional study involved 220 hypertensive patients. The outcome variables were assessed using biophysiological and biochemical methods.Association between socio-clinical variables with bio-physiological and biochemical parameters was done with the Mann-Whitney U test, ANOVA, Kruskal-Wallis ANOVA, and Spearman's correlation. p < 0.05 was considered statistically significant. Results: 71.36 % had hypertension for the past 10 years, 73.63 % were on anti-hypertensives for 10 years, and 80.91 % were prescribed a single drug. The median HDL and LDL levels were 58 mg/dL and 140 mg/dL, respectively.Weight emerged as a strong positive contributor to all three BP measures [systolic blood pressure (SBP): p = 0.026, diastolic blood pressure (DBP): p = 0.001, and mean arterial pressure (MAP): p = 0.001], highlighting its potential role in BP control. Gender disparities were evident, with men having higher DBP (p < 0.001) and MAP (p = 0.003) compared to women. Smoking habit was particularly detrimental, showing a significant association with higher DBP (p = 0.016). A link between heart rate and comorbid conditions (p = 0.044) suggests a potential interplay between weight, hypertension, and overall health. Linear regression analysis revealed a statistically significant positive association between weight, DBP, and MAP (p < 0.05 for both). Conclusions: Age showed a weak correlation, and weight management emerged as a crucial factor for BP control. Strategies to decrease weight would be crucial for the control of hypertension.